Increasing Student Responsibility in Revision Efforts: Redefining and Restructuring Peer Response with the Millennial Generation - Bickford, Crystal (Journal of Academic Writing, 2015)
The Millennial Generation presents a unique set of challenges to the classroom, including the desire to multi-task and teamwork as well as a strong need for attention and validation. Frequently, this creates a conflict between the students’ current skills and the teacher’s expectations when it comes to drafting and revision efforts. Restructuring traditional peer response methods into a group conferencing method allows students to utilize their current strengths while building skills necessary for later writing assignments. By participating in a six-step activity that occurs during a seventy-five minute class period, students are asked to listen, read, write, respond, discuss, and apply writing techniques. Over the semester, the author finds that students are invited into the writing discourse by developing vocabulary representative of global writing issues (development, transitions, paragraph structure, etc.) as well as that of grammar and mechanics. In the process, students learn how to trust their instincts and listen to others while participating in a methodical approach to decision-making.